(untitled) (Zaranie Śląskie, 2025)
The starting point for writing an article on modernist school buildings erected in the Silesian Province during the interwar period was information taken from the biographical note on Leon Dietz d’Army, an architect working in Katowice, who was credited with developing modular solutions for the construction of standardised buildings of this type. In the course of the research, it turned out that relatively late, in October 1937, the Silesian Provincial Office sent an identical letter to seven local architects inviting them to a meeting on this matter. Apart from the aforementioned d’Arma, the group included Tadeusz Michejda, Wojciech Soboń, Zbigniew Rzepecki, Kazimierz Sołtykowski, Odon Litawski and Tadeusz Łobos. Archival research has allowed for detailed findings to be made regarding the construction of a public school in Katowice-Zawodzie, designed by Leon Dietz d’Arma under the supervision of Lucjan Sikorski, which around 1930 was considered the most prestigious school construction project during a period of severe economic crisis. The history of this construction served as the basis for the conclusion that functionalism became the style of newly built schools not only because of the low cost of solutions that did not strive for decorativeness and were based on the use of cheap reinforced concrete technology, but also because of the involvement of local artists in the modern architectural movement. It should also be emphasised that the use of cost-effective technological solutions did not diminish the attention paid to teaching comfort. At that time, educational buildings with central heating, running hot and cold water, electric lighting, and even a swimming pool and a spacious gym for modern gymnastics were considered standard.